INEQUITY IN CHILDHOOD IMMUNIZATION BETWEEN URBAN AND RURAL AREAS OF PESHAWAR - Naeem, Mohammad; Khan, Muhammad Zia Ul Islam; Adil, Muhammad; Abbas, Syed Hussain; Khan, Muhammad Usman; Khan, Ayasha; Naz, Syeda Maria (Journal of Ayub Medical College Abbottabad, 2011)
Background: Purpose of this study was to find coverage of vaccines in EPI and compare the factors related to vaccine failure or missed vaccination in urban and rural areas of Peshawar. Methods: This cross-sectional survey was conducted in Urban and rural of Peshawar from 20th to 31st of June 2010. A questionnaire was used to interview parents of 548 children, aged 1 year and below, about demographics, vaccination status, reasons for missed vaccination and views on immunization. Results from both urban and rural areas were compared to find the impact of different factors on immunization failure. Results: The immunization coverage in urban areas was 76.5% while in rural areas it was 48.8%. Causes for non immunization were different in urban and rural areas. In urban areas, lack of awareness and care takers/parents being busy were the main reason for non immunization. In rural areas, in addition to formers, lack of accessibility to health centres and misconceptions about vaccination were major reasons for non-immunization. Parents were more educated in urban areas than rural areas. Conclusion: Rural areas had a lower immunization rates due to lack of awareness, low accessibility and much lower education of parents. Keywords: EPI Pakistan, children, immunization, urban, rural